Moderating Effects of Physical Activity and Global Self-Worth on Internalizing Problems in School-Aged Children With Developmental Coordination Disorder - Li, Yao-Chuen; Graham, Jeffrey D.; Cairney, John (Frontiers in Psychology, 2018)
School-aged children with Developmental Coordination Disorder (DCD) are at greater risk for physical inactivity, lower global self-worth, and internalizing problems, such as depression and anxiety. Based on the Environmental Stress Hypothesis (ESH), recent research has shown that physical inactivity and lower global self-worth sequentially mediate the relationship between DCD and internalizing problems, suggesting that DCD leads to lower levels of physical activity, which in turn, leads to lower levels of global self-worth, and ultimately, a greater amount of internalizing problems. However, physical activity and global self-worth may also buffer (i.e., moderate) the adverse effect of DCD on internalizing problems. To date, this has yet to be tested. Participants were 1206 children aged 12-14 years (611 boys, 79 with probable DCD (pDCD)). All children received assessments of motor coordination, physical activity, global self-worth, and internalizing problems. Children with pDCD were less physically active, had lower self-worth, and experienced more internalizing problems compared to typically developing (TD) children (p’s < .05). Furthermore, the moderated moderating effect (three-way interaction) of physical activity and global self-worth was also evident (p < .05), indicating that internalizing problems in both TD and pDCD groups decreased with concurrent increases in physical activity and global self-worth. Importantly, when compared to TD children, increases in physical activity and global self-worth were associated with a greater reduction in internalizing problems among children with pDCD. The findings support several pathways in the ESH and highlight that, in addition to improving motor skills, interventions should also target both physical activity and global self-worth to mitigate potential mental health issues for children with motor difficulties.